An exploration of treatment seeking behavior of women experienced infertility and need for services in rural India - Patra, Shraboni; Unisa, Sayeed (Frontiers in Reproductive Health, 2022)
Background: To make informed decisions on fertility treatment, couples need to understand the treatment options available to them. A wide range of treatment options is available from the traditional and biomedical service providers in India. There is a dearth of research to find out factors that influence the treatment-seeking behavior of couples, particularly in rural areas. Objectives: The study aimed to document the treatment-seeking behavior of women for their infertility problems. Further, the research focused on the socio-economic determinants affecting allopathic treatment-seeking of women and the services needed for couples experiencing infertility in rural India. Methods: The study is cross-sectional. Primary data were collected from the two high infertility prevalence districts. Complete mapping and listing were carried out to identify the eligible respondents. A total of 159 ever-married women (20-49 years) out of 172 identified women were interviewed. Bivariate and multivariate analyses were performed. Results: Among 159 interviewed women, only three did not seek any kind of treatment. Of the 156 women, 63, 65 and 28 women (mutually exclusive) received first, second and third-order treatment respectively. The number of women decreased in the succeeding phases of infertility. Women aged above 35 years, were significantly less (OR=0.310, p<0.05) compared to women aged below 30 years to receive allopathic treatment. The use of allopathic treatment was significantly three times higher among women who were educated (OR=3.712, p<0.01) and two times higher among those who were exposed (OR=2.217, p<0.5) to media. Further, for those who had felt the treatment was necessary, about 30%, 44%, 10%, and 19% mentioned that due to unaffordability, inaccessibility, or inconveniences they couldn’t consult allopathic treatment. Conclusions: Timely diagnosis and appropriate treatment play important role in infertility management. Women, who are more educated and are exposed to media, tend to consult allopathic treatment. Similarly, time and money spent on care vary significantly and independently by type of treatment and socioeconomic factors. There is a need for mandatory insurance coverage for infertility treatment enacted by the state government. In addition to the public services, the private sector and the traditional healers are both important alternative sources of first help.